Challenges in implementation of asset management strategy in the Limpopo Department of Public Works, Roads and Infrastructure - Myeni, Mante Baatseba (My University, 2021)
The study aims to investigate challenges in implementation of asset management strategy in the Limpopo Department of Public Works, Roads and Infrastructure, in order to recommend possible alternatives to improve asset management in the department. The Department achieved qualified audit opinions on asset management from the regularity audit conducted by the Auditor General for the financial years 2013/14 to 2015/16, which indicate that there is a lack of compliance, ineffectiveness and inappropriateness of asset management systems within the Department. This study examines the effectiveness of asset management practices in the LDPWRI and to determine the challenges faced by the LDPWRI in the implementation of asset management strategy and also to recommend strategic interventions that should be undertaken to improve asset management in the department. The information obtained from the literature identified the procedure which is used to manage assets in South Africa, the implementation process of asset management, and policies applied in the LDPWRI. The research process in this study includes methods such as a qualitative and quantitative approach necessary to collect the data. Furthermore, interviews and questionnaires were used in assessing the attitude of the participants. The primary data from the participants was obtained by the researcher to understand behaviour, working conditions, and the asset management process by the employees. The data revealed various challenges that are prevalent in how the inventory, record keeping, and the implementation of the strategies are implemented. The results showed that there are major challenges in managing inventory, and the information of the inventory is not recorded. There is also poor record keeping of the inventory. Furthermore, while the employees indicated that there is asset management strategy, a few indicated that there is no asset management strategy. The recommendations include that Asset Management strategies should be communicated to all employees and easily accessible on the Intra-Net of the Department for ease of reference and consultation. Urgent drastic steps should be taken to ensure that vacancies in the Asset Management and Logistics Directorate are filled without fail and within the acceptable service standards as stipulated by DPSA.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Asset management; Asset management strategy; Limpopo Public Works; Government property -- South Africa -- Limpopo Province -- Management; Finance -- Public -- Management